P PENGARUH PEMBERIAN MADU LEBAH TERHADAP TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI - Natar Fitri Napitupulu (Cintra Bangsa University - Literacy and Publishing Center (CBU-LPC), 2020)
Abstract Hypertension is defined as persistent blood pressure where the systolic pressure is above 140 mmHg and the diastolic pressure is above 90 mmHg. One of the ingredients of honey to reduce blood pressure is flavonoids. The design used in this study was